Dying is never beautiful, but there are beautiful moments: qualitative interviews with those affected on the subject of 'good dying' - Heimerl, Katharina; Schuchter, Patrick; Egger, Barbara; Lang, Alexander; Frankus, Elisabeth; Prieth, Sonja; Kaelin, Lukas; Dinges, Stefan; Wegleitner, Klaus; Reitinger, Elisabeth (Mortality (Abingdon, England), 2023)
The concept of the good death has been widely considered. However, the perspectives of those affected have not received sufficient attention. In our empirical study, we conducted interviews with 32 people who were confronted with dying; these people were either terminally ill, elderly or else were bereaved carers. The findings show that for this group of people, dying is not just a physical process, but also a psychological, social and spiritual one. From the perspective of those affected, dying is never beautiful, in particular because of the associated pain and suffering. At the same time, people confronted with dying do experience beautiful moments. In the stories they tell of these beautiful moments, it is a beauty emanating from a sense of elevated emotion - of moral emotion - rather than any aesthetic beauty. We conclude that good care of the dying enables beautiful moments and creates reflective spaces for those affected to express what beauty means to them. We show that the public discourse differs significantly from the perspective of those affected and more efforts need to be made to include their voices.